STEM APPLICATIONS IN MATHEMATICS EDUCATION: THE EFFECT OF STEM APPLICATIONS ON DIFFERENT DEPENDENT VARIABLES - Yıldırım, Bekir; Sidekli, Sabri (Journal of Baltic science education, 2018)
The purpose of the research is to analyze the effect of STEM applications on mathematics pre-service teachers' mathematical literacy self-efficacy, technological pedagogical knowledge and mathematical thinking skills and their views on STEM education. This research has been carried out by 29 mathematics pre-service teachers who are schoolers at the educational faculties of Mus Alparslan University. The research was completed in 10 weeks (3 hours per week) in spring semester of 2016-2017 academic year. Mixed research approach was used in the study. "Mathematical Literacy Self-Sufficiency Scale", "Mathematical Thinking Scale", "Technological Pedagogical Area Information Scale" and "STEM Interview Form for Mathematics Pre-service Teachers" were used as data collection instruments. The collected data were analyzed, and it was certain that the STEM applications positively affected the pre-service teachers' mathematics literacy self-efficacy and technological pedagogical content knowledge. However, STEM applications were not seemed to have a positive effect on mathematical thinking. Moreover, when the opinions of the pre-service teachers were examined, it was identified that the STEM applications changed positively the opinions of the pre-service teachers about the mathematical literacy, and that they lacked many subjects such as field knowledge and pedagogy knowledge about STEM education. Suggestions were made in the direction of the findings obtained.